ACTIVE LEARNING STRATEGIES: EQUIPPING PRIMARY SCHOOL TEACHERS FOR 21ST CENTURY EDUCATION - Ika Agustina; Mohammad Ahmad Bani Amer; Najah Yousef Baroud (International Journal of Teaching and Learning, 2025)
21st century education demands a paradigm shift in the learning process, especially at the primary school level. Active learning strategies are emerging as an effective approach to prepare students for future challenges. This research aims to examine the importance of active learning strategies and how to equip primary school teachers with the necessary skills to implement them. Through literature review and analysis of best practices, this research identifies various effective active learning methods, such as project-based learning, collaborative discussion and technology integration. The results show that active learning not only increases student engagement, but also develops 21st century skills such as critical thinking, creativity, collaboration and communication. However, its implementation faces challenges such as limited time and resources, and the need for continuous teacher training.